Professional management in irrigation systems: a case study of performance control in Mahaweli System H, Sri Lanka - Raby, N.; Merrey, Douglas J. (International Irrigation Management Institute, 1989)
Taking System H of the Mahaweli Program in Sri Lanka as a case study, this paper investigates a field still largely unexplored - the agency and its capacity to manage an irrigation system.